Finding the right institutional and legal framework for community-based natural forest management: the Tanzanian case - Wily, L. (1997)
As community involvement in natural forest management expands and matures, the need to lodge the rights and obligations of both state and community in workable and legally binding institutional frameworks becomes more pressing. This is particularly so where power and authority are being redistributed. This publication looks specifically at Tanzania, where forest-local communities are beginning to be designated as the management authority of particular woodlands and, in some cases, even their owners. Positive results are giving considerable support to community-based management as the forest management strategy of choice. Implementation has of necessity also prompted a search for accessible mechanisms through which community authority may be embedded legally. The author argues that, in this respect, Tanzania has an advantage over many sub-Saharan African states in the unusual manner of legal identity granted to rural communities, and in supporting administrative and land laws which provide for village-based control over natural resource management. Specific elements explored include the fact that rural villages in Tanzania are recognised as a formal level of government, endowed thereby with certain rights and obligations; that the rural village may attain legal corporate status allowing it, inter alia, to own and manage property in ways accountable in a court of law; and that property law provides for a modern, statutory version of communal tenure, within the bounds and accountability of a private legal person. Wily provides a step-by-step guide to the ways in which a forest-adjacent community may secure custodianship over a local natural forest, whether it be an already gazetted Forest Reserve or public land forest, and be held accountable for sound conservationary management.